Pmr-1 gene affects susceptibility of Caenorhabditis elegans to Staphylococcus aureus infection through glycosylation and stress response pathways' alterations. Issue 1 (1st January 2019) - Schifano, Emily; Ficociello, Graziella; Vespa, Simone; Ghosh, Salil; Cipollo, John F; Talora, Claudio; Lotti, Lavinia Vittoria; Mancini, Patrizia; Uccelletti, Daniela
ABSTRACT: Calcium signaling can elicit different pathways involved in an extreme variety of biological processes. Calcium levels must be tightly regulated in a spatial and temporal manner in order to be efficiently and properly utilized in the host physiology. The Ca 2+ -ATPase, encoded by pmr-1 gene, was first identified in yeast and localized to the Golgi and it appears to be involved in calcium homeostasis. PMR-1 function is evolutionary conserved from yeast to human, where mutations in the orthologous gene ATP2C1 cause Hailey-Hailey disease. In this work, we used the Caenorhabditis elegans model system to gain insight into the downstream response elicited by the loss of pmr-1 gene. We found that pmr-1 knocked down animals not only showed defects in the oligosaccharide structure of glycoproteins at the cell surface but also were characterized by reduced susceptibility to bacterial infection. Although increased resistance to the infection might be related to lack of regular recognition of C. elegans surface glycoproteins by microbial agents, we provide genetic evidence that pmr-1 interfered nematodes mounted a stronger innate immune response to Gram-positive bacterial infection. Thus, our observations indicate pmr-1 as a candidate gene implicated in mediating the worm's innate immune response.